EVALUATION OF CHANGES IN VISUAL ACUITY AND CONTRAST SENSITIVITY IN PATIENTS WITH KERATOCONUS AFTER CORNEAL COLLAGEN CROSS-LINKING: Visual Acuity and Contrast Sensitivity - Javaid, Hassaan; Zafar, Omar; Akram, Seemal; Khan, Asfandyar; Abbas, Sana; Rafique, Aisha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate changes in visual acuity and contrast sensitivity in patients with keratoconus after corneal collagen cross-linking.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan, from May 2019 to Apr 2020.Methodology: A total of 48 eyes of 30 patients with progressive keratoconus were included in this study. Baseline uncorrected distance visual acuity, corrected distance visual acuity and contrast sensitivity were recorded, following which transepithelial corneal collagen cross-linking with topical riboflavin and ultraviolet A light was performed. Uncorrected distance visual acuity, corrected distance visual acuity and contrast sensitivity measurements were repeated and recorded 6-months postoperatively.Results: Mean preoperative uncorrected distance visual acuity was 0.56 ± 0.27 logarithm of the minimum angle of resolution which improved to 0.51 ± 0.26 at 6 months after the procedure (p=0.002). Mean corrected distance visual acuity was 0.30 ± 0.19 preoperatively, improving to 0.24 ± 0.18 (p=0.001) at 6 months after corneal collagen cross-linking, thereby depicting a statistically significant improvement. Treated eyes also showed a significant improvement in contrast sensitivity (p=0.001) of 0.05 ± 0.08 logarithmic units of contrast sensitivity, from a mean preoperative contrast sensitivity of 1.72 ± 0.10 to 1.77 ± 0.09 when evaluated 6 months after corneal collagen cross-linking.Conclusion: Corneal collagen cross-linking is a promising advancement in the treatment of keratoconus. It was found effective in significantly improving visual acuity as well as contrast sensitivity, thus enhancing visual outcomes in keratoconus.